The Role of Family Functionality and Its Relationship with Psychological Well-Being and Emotional Intelligence in High School Students - Pablo Molina Moreno; Silvia Fernández Gea; María del Mar Molero Jurado; María del Carmen Pérez-Fuentes; José Jesús Gázquez Linares (MDPI AG, 2024)
Adolescence is acknowledged as a critical transition stage in human development, during which factors such as family environment, psychological well-being, and emotional competencies are deemed crucial for optimal growth. Objective: A descriptive study with a quantitative, correlational, and cross-sectional approach was conducted to investigate: (1) how psychological well-being, emotional intelligence, and levels of family functioning are associated with each other; (2) the presence of gender disparities in psychological well-being, emotional intelligence, and family functioning; and (3) the identification of significant differences in psychological well-being and emotional intelligence based on family functioning. Methods: Participants were recruited from six different high schools in Spain. In total, 1092 secondary school students (584 females and 508 males) aged 12-17 years (M = 14.15) completed a series of instruments that were administered in person. Subsequently, data were statistically analysed and processed. Results: A positive correlation between family functioning, psychological well-being, and emotional intelligence was observed. In addition, significant gender differences were found in measures of psychological well-being, emotional intelligence, and family functioning. Finally, higher mean scores were identified for the high-functionality group when compared to the moderate-functionality and severe-dysfunctionality groups in both psychological well-being and emotional intelligence measures. Conclusions: The authors conclude by considering the family context as a key factor in adolescent development and propose future practical applications, such as programmes aimed at improving psychological well-being.